Beauty, Productivity, and Discrimination: Lawyers' Looks and Lucre - Biddle, Jeff E.; Hamermesh, Daniel S. (Journal of Labor Economics, 1998)
The authors propose models with an ascriptive characteristic generating earnings differentials and causing sectoral sorting, allowing them to distinguish among sources producing such differentials. They use longitudinal data on a large sample of graduates from one law school and measure beauty by rating matriculation photographs. Better-looking attorneys who graduated in the 1970s earned more than others after five years of practice, an effect that grew with experience. Attorneys in the private sector are better-looking than those in the public sector, differences that rise with age. These results support theories of dynamic sorting and customer behavior. Copyright 1998 by University of Chicago Press.